2003
DOI: 10.1161/01.hyp.0000085193.25617.78
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between ACE and ADD1 Gene Polymorphisms in the Progression of IgA Nephropathy in Japanese Patients

Abstract: Abstract-An interaction effect between the angiotensin-converting enzyme insertion/deletion (ACE I/D) and ␣-adducin (ADD1) Gly460Trp polymorphisms (G460W) on blood pressure regulation has recently been suggested, although its significance in the prognosis of renal function in IgA nephropathy (IgAN) has not been fully investigated. Therefore, we evaluated the clinical manifestations and renal prognosis in 276 Japanese patients with histologically proven IgAN with respect to their ACE I/D and ADD1 G460W polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
15
2
Order By: Relevance
“…Consistently, Wang et al (96) observed that, in 1454 subjects randomly selected from a white population, those with the combined presence of the W and D alleles of the ADD1 G460W and ACE I/D polymorphisms, respectively, were at increased risk of renal disease. The WW genotype was also associated with faster progression in Japanese patients with IgA nephropathy when combined with the II ACE genotype (97). Thus, the above preliminary findings provide some evidence that polymorphisms of components of non-RAS pathways, in combination with different ACE I/D genotypes, may affect the risk of development and progression of chronic kidney disease.…”
Section: Other Non-ras Polymorphisms and Their Interactions With The mentioning
confidence: 64%
“…Consistently, Wang et al (96) observed that, in 1454 subjects randomly selected from a white population, those with the combined presence of the W and D alleles of the ADD1 G460W and ACE I/D polymorphisms, respectively, were at increased risk of renal disease. The WW genotype was also associated with faster progression in Japanese patients with IgA nephropathy when combined with the II ACE genotype (97). Thus, the above preliminary findings provide some evidence that polymorphisms of components of non-RAS pathways, in combination with different ACE I/D genotypes, may affect the risk of development and progression of chronic kidney disease.…”
Section: Other Non-ras Polymorphisms and Their Interactions With The mentioning
confidence: 64%
“…Twelve (8,9,14,48,106,110,111,117,118,148,150,155) of 16 (103,107,115,162) studies found that ADD1 polymorphism alone or in combination with that of ACE positively associates with stroke or coronary heart disease or renal or vascular dysfunctions. In conclusion, when context is taken into account, the results obtained both in rats and in humans are consistent with the notion that the interaction among the adducin loci or between ADD1 and ACE are involved in human and rat hypertension and related disorders.…”
Section: Studies In Humansmentioning
confidence: 99%
“…[3] Several studies about the ACE I/D gene polymorphisms in VUR patients have revealed that the D allele might be a risk factor for renal parenchymal damage in children. [7][8][9] Also, the DD genotype has been reported to be associated with reduced renal function in patients with chronic renal diseases like Ig A nephropathy, [10][11][12] focal segmental glomerulosclerosis, [13,14] diabetic nephropathy, [15,16] polycystic kidney disease, [17] and tubulointerstitial nephritis. [18] Because tubulointerstitial damage is also common in VUR, the ACE polymorphism is of interest in this patient group, as it may give clues about the progression of the renal scarring.…”
Section: Introductionmentioning
confidence: 99%